The Effect of Self-Care Counseling on Health Practices of 35-Year-Old or More Aged Pregnant Women Referring to Hamadan Health Care Centers, in 2018 - Soodabeh Aghababaei; Fereshteh Omidifard; Ghodratollah Roshanaei; Parisa Parsa (Hamadan University of Medical Sciences, 2020)
Introduction: Maternal age of 35 years or older can be a risk factor for a significant increase in pregnancy complications. The aim of this study was to determine the effect of self-care counseling on the health practices in pregnant women aged 35 or older who referred to Hamadan comprehensive health centers. Methods: A randomized controlled clinical trial study was performed on 100 pregnant women aged 35 years and over referring to Hamedan health centers in 2018. The research instrument was a demographic questionnaire, and Health practices questionnaire that completed both groups before and after the intervention. The type of allocation of people in each clinic was done randomly using a random number table. The test group received consultation sessions. Data analysis was performed using SPSS 20 and (P<0.05) was considered significant. Results: According to the results, the mean scores of health practices in the test group before and after the intervention changed from (110.38±20.41) to (120.82±19.36) and the difference was statistically significant (P<0.05), while in the control group changed from (112.12±20.91) to (113.54±16.33) and the difference was not statistically significant (P>0.05). Conclusion: The present study showed the health practices of maternal aged in high risk pregnant women.